HUBUNGAN KUALITAS PELAYANAN LARISSA AESTHETIC CENTER SEMARANG DAN MANFAAT KEPEMILIKAN MEMBER CARD PRIVILEGE TERHADAP LOYALITAS PELANGGAN - A'yun, Ovika Khurrota (Interaksi: Jurnal Ilmu Komunikasi, 2017)
ABSTRACTLarissa Aesthtetic Center is one of the beauty and skin care clinics in Semarang City. They perform a variety of ways loyalty program that is wrong through the membercard. As performed by Larissa Aesthetic Center Semarang who issued Privilege membercard where many benefits that can be obtained by consumers. This research is intended to know the service quality of Larissa Aesthtetic Center Semarang to customer loyalty and also to know the relation of member privilege to customer loyalty. The theory used to support this research is Servqual theory. This research is type of explanatory research with sample of 100 customer of Larissa Semarang taken by purposive sampling technique. While the data analysis is done by Kendall Tau-b wake test. The result of hypothesis test shows that there is a correlation between service quality of Larissa Aesthetic Center Semarang with Customer Loyalty with significance value equal to 0,000 <0.05 and the result value of 0.379 indicates a weak relationship with customer loyalty. Thus, the hypothesis that the relationship between service quality and customer loyalty is accepted. Furthermore, the benefits of membercard privillege have a significance value of 0.000 <0.05 and a value of 0.303 indicating a weak relationship with customer loyalty. Thus, the hypothesis stating the relationship between the benefits of membercard and customer loyalty is accepted. The suggestion given is that Larissa can improve the service quality so that it is expected to build or increase customer loyalty.Keywords: Quality of Service, Member Card, Customer Loyalty